Could a terminal-based operating model reduce greenhouse-gas emissions in road transport of timber? - Anttila, Perttu; Väätäinen, Kari (Taylor & Francis, 2026)
Given the trucking companies’ need to reduce fuel consumption and greenhouse gas (GHG) emissions during timber transport, efficient operating models are crucial. While multimodal transport is preferred for long distances, road transport remains the primary method in regions lacking rail or waterway connections. This study evaluated whether a terminal-based operation model could reduce GHG emissions in road transport of timber. A discrete-event simulation model was used to compare traditional direct timber deliveries with a terminal-based system in northern Finland. The results showed that the integration of a terminal increased transport efficiency, allowing a 10% higher timber volume to be delivered. At the same time, the fuel consumption and GHG emissions of the supply system were reduced by 4% per cubic meter of timber transported. The benefits stem from more efficient trucking with shorter trips and more frequent full truck loads from a single storage location with mixed-assortment loads. Although terminal-based logistics requires investment and introduces additional handling costs, the study suggests that it can enhance sustainability and operational efficiency. The findings highlight the potential for emission savings, but further research is needed to assess the economic feasibility of the terminal-based operating model and the impact of alternative trucks in outbound logistics. The simulation model can be adapted to other environments to evaluate broader applicability.
Keywords: simulation; timber supply; pulpwood; timber terminal; log truck